Development of rule-based advisory system from modified hazard and operability study on fatty acid fractionation column - Mohd. Yusri Mohd. Yunus; Mohamad Wijayanuddin Ali; Mohd. Zaki Kamsah; International Conference on Chemical & Bioprocess Engineering (2003 : Universiti Malaysia Sabah, Sabah) (Skudai : Universiti Teknologi Malaysia, 2003)
50